History of the Surgical Research Laboratory of the University of Puerto Rico - Cruz, Norma I.; Santiago-Delpín, Eduardo A. (Puerto Rico Health Sciences Journal, 2025)
Objective: The history of the University of Puerto Rico (UPR) Surgical Research Laboratory was reviewed from its founding in 1952, by Dr. Francisco Raffucci, to the present. Method: The information for this overview was obtained from the annual reports written by the surgical laboratory directors. Interviews with surgeons who worked in the early facilities, and published works, provided the early history for which no annual reports were available. Results: The history of the laboratory begins at the former School of Tropical Medicine, under the direction of Dr. Francisco Raffucci (1952–1964). The laboratory was housed in a small building on the school grounds. Research in cardiovascular surgery, shock and transplantation was performed and published. The facility was later moved to a wooden building at the Medical Center, a medical complex in San Juan, Puerto Rico and was directed by Dr. Leovigildo Cuello (1964–1967), followed by Dr. Gerhart Ramírez Schon (1969–1972). Under Dr. Eduardo Santiago-Delpín (1972–1977) the laboratory was moved to the tenth floor of the UPR School of Medicine. Subsequent directors of the laboratory at the school of medicine were Dr. Pedro Roselló (1977–1983), Dr. Norma Cruz (1983–2004), Dr. Manuel Más (2000–2015), Dr. Aura Delgado (2015–2017), Dr. Enrique Márquez (2017–2018) and Dr. Anwar Abdul-Hadi (2018–2024), who still leads the laboratory. Currently, the facility is used in collaboration with equipment manufacturers as a surgical simulation center and on various research. Conclusion: The Surgical Research Laboratory continues training surgeons to use new surgical devices and supporting research projects.